Closed‐PICU perioperative management of congenital tracheal stenosis. Issue 1 (26th May 2022) - Aoki, Kazunori; Kurosawa, Hiroshi; Seino, Yusuke; Morita, Keiichi; Matsuhisa, Hironori; Oshima, Yoshihiro
Abstract: Background: Perioperative management of congenital tracheal stenosis (CTS) is challenging. In the present study, compared the effect of closed‐pediatric intensive care unit (PICU) perioperative management by pediatric intensivists and open‐PICU management by surgeons. Outcomes in terms of ventilator‐free days (VFD) and length of postoperative PICU stay in children with CTS were evaluated. Methods: This retrospective cohort study was conducted in a PICU in Japan. Children with CTS who underwent slide tracheoplasty were grouped according to whether they were perioperatively managed in an open (January 2015 to April 2016) or a closed (May 2016 to August 2019) PICU. Data were extracted from patients' medical records. Results: In total, 13 and 38 patients were included in the open‐ and closed‐PICU groups, respectively. Compared to the open‐PICU group, the closed‐PICU group had shorter duration of muscle relaxant administration (median 4 vs 5 days; P < 0.001), earlier enteral nutrition (34/38 [90%] vs 1/13 [8%]; P < 0.001), more 28‐day VFD (median 21 vs 20 days; P = 0.04), and shorter duration of postoperative PICU stay (median 16 vs 36 days; P = 0.002), but mortality did not differ significantly between the two groups (0/38 [0%] vs 1/13 [8%]; P = 0.25). Conclusions: Closed‐PICU perioperative management with pediatric intensivists' participation significantly increased 28‐day VFD and reduced the length of postoperative PICU stay in patients with congenital tracheal stenosis.